2019
DOI: 10.1021/acs.cgd.8b01771
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Azilsartan with Acidification of Azilsartan Disodium Salt

Abstract: A reactive crystallization process induced by acidification of azilsartan disodium salt was proposed to produce sub-micron-sized crystals. In the present work, azilsartan crystals were obtained by mixing two aqueous solutions of azilsartan disodium salt (ADS solution) and acetic acid (AA solution). When ADS solution was injected into AA solution, the crystalline azilsartan (type I), the thermodynamically stable form, could be obtained by the phase transformation of amorphous intermediates of azilsartan initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The CLD was measured with focused beam reflectance measurement (FBRM, made by Mettler Toledo International Inc., Columbus, OH, USA). The FBRM technique is often applied to obtain the size distribution [19][20][21]. However, the CLD obtained with FBRM is different from CSD, and hence, the CLD needs to be converted into the CSD [22,23].…”
Section: Substances and Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLD was measured with focused beam reflectance measurement (FBRM, made by Mettler Toledo International Inc., Columbus, OH, USA). The FBRM technique is often applied to obtain the size distribution [19][20][21]. However, the CLD obtained with FBRM is different from CSD, and hence, the CLD needs to be converted into the CSD [22,23].…”
Section: Substances and Devicesmentioning
confidence: 99%
“…Fourthly, the derivation of the second step is substituted into that of the third step, and the relation between the µ 3,seed and the averaged µ 3 is derived. Finally, the derivation of the fourth step is substituted into Equation ( 20) at i = 0, and this equation is integrated with t substituted by ∆T/R to derive Equation (21). Here, ∆T is a decrease in the solution temperature.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…The FBRM measuring range was 0-1000 μm and was divided into 100 equal parts by a linear scale. Not the CSD but the chord length distribution (CLD) can be directly determined by FBRM [17][18][19]. However, the CLD can be converted into the CSD with statistical methods via a mapping matrix based on the crystal shape [20][21][22].…”
Section: Substances and Devicesmentioning
confidence: 99%
“…In reactive crystallization, only the target product can crystallize from the solution and the reactants and byproducts remain in solution by selecting appropriate system conditions, and the driving force for crystallization of the target product is created by its synthesis . Thus, reactor type, temperature, , concentration of the reactants, , feed profile, reaction time, additive, and many other factors that influence the reaction process and crystallization process may have a fundamental effect on the quality of the final crystals such as crystal phase, morphology, and particle size. The reactive crystallization mechanism and the process development of the industrial materials has been investigated widely.…”
Section: Introductionmentioning
confidence: 99%
“…PVM, attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy, and focused beam reflection measuring (FBRM) were the mostly used process analysis tools to investigate the kinetics of reactive crystallization. Kim et al 14 applied ATR-FTIR and FBRM to investigate the effect of temperature and dissolution time on the particle size of azilsartan disodium salt from reactive crystallization induced by acidification, and the dissolution time for amorphous intermediates was found to be the key factor that determines the final particle size. Zhao et al 15 applied a laser method to investigate the effect of supersaturation and temperature on the nucleation mechanism of the reactive crystallization of lithium carbonate and found that heterogeneous nucleation and the homogeneous nucleation governs by supersaturations and temperature.…”
Section: Introductionmentioning
confidence: 99%